Development of a prognostic RiskScore model using efferocytosis-related signature genes for lung adenocarcinoma - Dai, Zengmin; Jin, Shaofeng; Huang, Shanshan; Liu, Bingyang; Shen, Xingkai; Jin, Yuhong (PeerJ, 2025)
Background Lung adenocarcinoma (LUAD) has high incidence and mortality rates. Efferocytosis is involved in the progression of various cancers. The current work set out to develop a prognosis signature using efferocytosis-related genes (ERGs) for LUAD. Methods Public databases were accessed to obtain bulk and single-cell data of LUAD. Molecular subtyping of LUAD was performed using ConsensusClusterPlus, and efferocytosis-related candidate genes were screened by weighted gene co-expression network analysis (WGCNA) in combination with differential analysis. Subsequently, Least Absolute Shrinkage and Selection Operator (LASSO) regression was applied to construct a prognostic RiskScore model, followed by evaluating the relationship between the RiskScore, immune infiltration, and drug sensitivity. Single-cell transcriptomic profiling of LUAD was performed with the Seurat package to elucidate the cellular origins of the key genes. The expression and potential function of the representative genes were verified by reverse transcriptional quantitative polymerase chain reaction (qPCR) (RT-qPCR), Cell Counting Kit-8 (CCK-8), wound healing, and Transwell assays. Results Two molecular subtypes of LUAD with different outcomes and clinical features were identified. Candidate ERGs were mainly enriched in inflammatory and immune-related pathways. Subsequently, seven key genes (CD200R1, BTN2A2, STAP1, DNASE2B, SAMD9, SEMA7A, BIRC3) associated with efferocytosis in LUAD were identified to establish a RiskScore model, which exhibited high robustness in predicting patient prognosis. Notably, high-risk group had lower immune scores and more unfavorable prognosis than low-risk group. Moreover, eight drugs were closely linked to the RiskScore, and low-risk group was more sensitive to Doramapimod_1042. Single-cell atlas of LUAD showed that the prognostic ERGs were mainly expressed in mast cells. In vitro experiments revealed that most of the seven ERGs were overexpressed in LUAD cells, and that SEMA7A knockdown could suppress LUAD cell proliferation, migration and invasion. Conclusions Our results provided novel insights for the prognosis prediction and personalized treatment of LUAD.
Keywords: Efferocytosis; Lung adenocarcinoma; RiskScore model; Prognostic signature; Immune infiltration; Drug sensitivity